Dimensions of Burnout Syndrome: in Service Primary and Pre-primary Teachers' Views in Achaia - Γκάμαρη, Mάρθα; Φωτοπούλου, Βασιλική Σ. (Education Sciences, 2025)
This study seeks to highlight individual aspects of the burnout syndrome and to contribute through this approach to a deeper understanding of it and to addressing the challenges of teachers in the contemporary educational context. The aim of this study is to investigate the differences between the dimensions of burnout and the correlations of demographic characteristics with them, using the Maslach Burnout Inventory (MBI) research tool. The research sample consisted of in-service primary and pre-primary teachers in Achaia and the data was collected using an anonymous self-completion questionnaire. From the responses it is found that there are variations in the dimensions of burnout syndrome, which are characterized as moderate and high. In particular, the scale of emotional exhaustion shows moderate (towards high) levels, the scale of depersonalization shows medium levels, and the scale of personal achievements registers high levels. Still, some demographic characteristics, such as teachers' teaching experience, their satisfaction with their income or gender seem to be related to burnout syndrome. This paper seeks to highlight individual aspects of teachers' burnout syndrome to contribute through this approach to a deeper understanding of the syndrome and to address the challenges of teachers in the contemporary educational context.